2011
DOI: 10.1177/0093650210376191
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Test of a Cognitive-Emotional Theory of Esteem Support Messages

Abstract: Esteem support is a form of social support that is provided to others with the intent of enhancing how they feel about themselves. This article outlines and assesses empirically a cognitive-emotional theory of esteem support messages (CETESM), which identifies (a) dimensions along which esteem support messages can be scaled, (b) mechanisms through which sophisticated esteem support messages should have their effects, and (c) outcomes that should be generated by messages that vary in quality. The merits of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 44 publications
6
101
0
Order By: Relevance
“…Consistent with this hypothesis, an initial test of the CETESM found that high emotion-focused messages were rated as better at enhancing perceptions of state selfesteem than messages low in emotion focus (Holmstrom & Burleson, 2011).…”
Section: Message Qualitymentioning
confidence: 84%
See 1 more Smart Citation
“…Consistent with this hypothesis, an initial test of the CETESM found that high emotion-focused messages were rated as better at enhancing perceptions of state selfesteem than messages low in emotion focus (Holmstrom & Burleson, 2011).…”
Section: Message Qualitymentioning
confidence: 84%
“…An initial test of the CETESM (Holmstrom & Burleson, 2011) investigated the effectiveness of messages that were theorized to be more and less sophisticated, as well as the outcomes that may be associated with esteem support messages of differing quality. For the most part, theoretical predictions were supported.…”
mentioning
confidence: 99%
“…." Holmstrom & Burleson, 2011). Thus, friends' supportive responses (i.e., acceptance) and influence techniques (i.e., challenge; Lewis & Butterfield, 2007;Markey, Markey, & Gray, 2007) may facilitate others thinking differently about themselves and their behaviors.…”
Section: Confronting Co-rumination: Confirmation Theorymentioning
confidence: 99%
“…Depending on characteristics of specific support situation, such as causes of stress, emotional support may be manifested as esteem support, which focuses on helping the target maintain or restore selfesteem or positive self-identity through verbal and/or nonverbal expressions of concern, affection, reassurance, and positive appraisal (Collins & Feeney, 2004;Cramer, 2003;Weisz & Wood, 2005;Wills, 1985). Therefore, in this study, emotional support is viewed as encompassing esteem support (Dakof & Taylor, 1990;Graetz, Shute, & Sawyer, 2000;Holmstrom & Burleson, 2011).Substantial research has documented the salutary effects of sensitive emotional support on the physical and psychological well-being of individuals, as well as the maintenance and development of personal relationships (e.g., Acitelli, 1996;Burleson, Kunkel, Samter, & Werking, 1996;Samter, 1994;Whitbeck, Hoyt, & Huck, 1994). Correspondingly, the provision of emotional support has been consistently evaluated as a helpful and appropriate response to an individual's stress across a wide range of situations, and across cultures (for reviews, see Feng & Burleson, 2006;MacGeorge et al, 2011).…”
mentioning
confidence: 99%